(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This research explores the pragmatic and cross-cultural aspects of communication by comparing speech acts and politeness strategies in English, Uzbek, and Russian. The study focuses on five key areas: (1) forms of address, (2) etiquette expressions, (3) apology strategies, (4) complimenting and criticizing patterns, and (5) direct and indirect speech acts. Through discourse analysis and questionnaire-based data collection, the study aims to identify cultural norms and pragmatic tendencies that shape interpersonal communication in each language. The findings highlight how linguistic politeness reflects cultural values such as individualism and collectivism, respect for hierarchy, and degrees of formality. This comparative typology contributes to understanding intercultural pragmatics and enhances communicative competence in multilingual and multicultural contexts.